Transient Bone Marrow Edema Syndrome (Case Report) - Nilnur Konuralp; Devrim Meydan Ocak; Berrin Albayrak; İlyas Tutar; Cihangir Yurtoğlu; Cemal Kocabaşoğlu; Ali Rıza Aydoğan; Leyla Kılıç Atakanlı; Hayri Özgüzel (Türk Osteoporoz Dergisi, 2003)
Transient bone marrow edema syndrome (BMES) is accepted as a possible cause of acute disabling hip pain. This syndrome is defined as local osteoporosis in hip in radiographies, BME in MRI which can be rarely seen and has a self-limiting course. Although the disease generally has a self-limiting course, surgical treatment by early core decompression of the femoral head has proven effective in rapidly relieving the symptoms. Although BMES is relatively rare and probably underdiagnosed when compared to nontraumatic osteonecrosis, both conditions are associated with known osteonecrosis risk factors in middle aged men and especially with late (thirdhad trimester) pregnancy in women. We have reported three cases with BMES that had different etiology and followed up presented the differential diagnosis to nontraumatic avascular osteonecrosis. These three cases were treated in early stage very succesfully.